N α -arylsulfonyl histamines as selective β-glucosidase inhibitors - Salazar, Mario Oscar (2018)
Nα-benzenesulfonylhistamine, a new semi-synthetic β-glucosidase inhibitor, was obtained by bioactivity-guided isolation from a chemically engineered extract of Urtica urens L. prepared by reaction with benzenesulfonyl chloride. In order to identify better β-glucosidase inhibitors, a new series of Nα,Nτ-di-arylsulfonyl and Nα-arylsulfonyl histamine derivatives was prepared. Biological studies revealed that the β-glucosidase inhibition was in a micromolar range for several Nα-arylsulfonyl histamine compounds of the series, Nα-4-fluorobenzenesulfonyl histamine being the most powerful compound. Besides, this reversible and competitive inhibitor presented a good selectivity for β-glucosidase with respect to other target enzymes including α-glucosidase.